Cationic [6]Helicenes: Tuning (Chir)Optical Properties up to the Near Infra-Red. (2022) - Bosson, Johann; Labrador, Geraldine M.; Jacquemin, Denis; Lacour, Jérôme
Abstract: The intramolecular condensation of ortho substituents of triaryl carbenium ions can lead to the formation of cationic helicenes. These chiral and configurationally stable molecules exhibit extended optical properties reminiscent of their parent methylium ions. Among them, cationic [6]helicenes are particularly interesting as orthogonal late-stage functionalization strategies allow the introduction of a variety of auxochromes with different regiochemistry. Intense chiroptical properties can thus be tailored in the far red and up to the near infra-red (NIR) spectral windows. A wealth of applications can be foreseen, in particular in material sciences.